NEEDS ANALYSIS OF THE USE OF INQUIRY BASED LEARNING MODELS IN LEARNING ENGLISH FOR KINDERGARTEN STUDENTS - Nur Amaliah; Jusmaniar N; Dahniar Dahniar (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
This study aims to analyze the need for implementing an Inquiry-Based Learning (IBL) model in teaching English to kindergarten students. This research uses a qualitative descriptive method with data collection through observation sheets and teacher interviews. The research focused on Class B1 of Annur Manggala Kindergarten, involving 16 students as observation subjects and their teachers as interview respondents. The needs of learning English with IBL methods for kindergarten involve several key aspects, 1) Necessities including of appropriate learning resources, classroom environment, and teacher support. While, although research found that the school has made significant necessities in implementing IBL, 2) the lacks which challenges such as limited access to supporting materials, restricted classroom space, and minimal integration of technology affect the overall learning experience. 3) The classroom environment supports most of the key aspects wants for Inquiry-Based Learning, particularly in terms of student engagement, teacher support, and access to hands-on, creative materials.